“El Cumplimiento Tributario y su Impacto en la Rentabilidad del Hotel “Bravo” del Cantón Quevedo, periodo 2019”. - Villegas Napa, Mariana Elizabeth (2020)
This investigation analyzed tax compliance and its impact on the profitability of the "Bravo" hotel in the Quevedo canton. The study was carried out based on the problems associated with non-compliance with tax contributions and the country's legal provisions as part of a growing anti-value culture. The information in this study is based on relevant texts and documents about the variables established in the topic. The applied methodology is qualitative, descriptive and correlational of the transversal type with a focus on the description of the problems related to tax compliance, the information collection techniques used were the survey and the interview, through a questionnaire it was possible to obtain direct information of those involved in the project. From the results obtained, it is observed that there are limitations to the information provided by the interviewees because the documents are not clear, ordered, in some cases no invoices have been issued, this evidences an effect on the tax burden, which is why it is concluded according to The information obtained in this investigation, the hotel, the accounting system has not yet been improved, which may incur in cases of non-compliance with tax obligations on time. In addition, it is found that if you meet the tax obligations based on your income and expenses.